Social leisure time activities as a mediating link between self-reported psychological symptoms in adolescence and psychiatric morbidity by young adulthood: the Northern Finland 1986 Birth Cohort study. - Timonen, Johanna; Niemelä, Mika; Hakko, Helinä; Alakokkare, Anni; Räsänen, Sami (European Child & Adolescent Psychiatry, 2023)
Research indicates that adolescent psychological symptoms are associated with subsequent mental health disorders. Studies also show the association of leisure activity with improved current and future mental health. However, research is limited on whether social leisure time activity is a mediating link in the association between psychological symptoms and later psychiatric morbidity. We examined whether adolescence-related social leisure time activity, per se, is a mediating link in the association between adolescent psychological symptoms and later psychiatric morbidity. The study population was based on the Northern Finland Birth Cohort 1986 Study (NFBC 1986; n = 6709; 3227 males). Psychological symptoms at age 15–16 years were measured with the Youth Self Report (YSR) questionnaire. Study participants' psychiatric morbidity by the age of 33 years was assessed using the diagnoses from the nationwide health care registers. Our results showed an association between psychological symptoms and leisure time activities that varied depending on the level of social activity. Leisure time activity was found to be a mediating link between psychological symptoms in adolescence and psychiatric disorders in early adulthood. Adolescence-related leisure time activities, which differed with regard to social interactions, appeared to serve as a mediating link between adolescent psychological symptoms and later onset of psychiatric disorders. Socially active leisure time during adolescence is related to better long-term mental health, while socially inactive leisure time associates with the likelihood of later psychiatric morbidity. To prevent psychiatric disorders, enhancing such leisure time activities in society is highly recommended.